SISTEM INFORMASI INVENTARIS BARANG PADA LABORATORIUM SMK NEGERI 5 SAMARINDA - Arnada Cinta Belena; Tina Tri Wulansari; Riyayatsyah (METIK JURNAL, 2020)
Computer technology is needed everywhere including inventory activities. The existence of inventory activities can minimize defects or obscurity of each device starting from the data collection of the device entering and exiting device, data collection of consumable and non-consumable device, data collection of damaged device or items that must be destroyed. But so far the inventory activities at the SMK Negeri 5 Laboratory have not been going well and the reporting process is very ineffective. Assist in research made by the Inventory Information System of Device that will assist administrative staff, laboratory personnel and principals in inventory activities. This system was designed using the prototyping system development method. Whereas the programming language used is Visual Basic and SQL Server 2008 databases. Principals, laboratories responsible, and administrative staff have their user access according to their respective user access rights according to the access rights specified by the system administrator. These data can produce reports on receipt, utilization, transfer, and maintenance of a device. Help reduce delays in reporting by organizing data collection and making inventory reports.